2000
DOI: 10.1098/rspb.2000.1177
|View full text |Cite
|
Sign up to set email alerts
|

Sperm competition games played by dimorphic male beetles: fertilization gains with equal mating access

Abstract: Alternative mating tactics can generate asymmetry in the sperm competition risk between males within species. Theory predicts that adaptations to sperm competition should arise in males facing the greater risk. This prediction is met in the dung beetle Onthophagus binodis where minor males which sneak copulations have a greater expenditure on the ejaculate. In its congener Onthophagus taurus there is a reduced asymmetry in sperm competition risk such that both tactics have equal ejaculate expenditure. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 41 publications
3
55
1
Order By: Relevance
“…First, we found that, on average, alternative tactics yielded unequal ¢tness; major males obtained 11% of fertilizations compared with only 2.5% for minor males. This undoubtedly re£ects di¡erential mating access since, with equal access to fertilization, success does not vary between morphs (Tomkins & Simmons 2000). Second, where the ¢tness functions of two alternative tactics are themselves linear, status-dependent selection should generate a ¢tness function across the full range of male phenotypes that is nonlinear and that will have a change in slope where alternative ¢tness functions intercept (¢gure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…First, we found that, on average, alternative tactics yielded unequal ¢tness; major males obtained 11% of fertilizations compared with only 2.5% for minor males. This undoubtedly re£ects di¡erential mating access since, with equal access to fertilization, success does not vary between morphs (Tomkins & Simmons 2000). Second, where the ¢tness functions of two alternative tactics are themselves linear, status-dependent selection should generate a ¢tness function across the full range of male phenotypes that is nonlinear and that will have a change in slope where alternative ¢tness functions intercept (¢gure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…Copulation lasts for 2-3 min (Tomkins & Simmons, 2000) during which females are unable to continue provisioning. We found that increasing the frequency of sneaks in the population increased the total number of copulations performed by a female.…”
Section: Costs and Benefits Of Extra-pair Copulationsmentioning
confidence: 99%
“…First, females store sperm and mate with multiple males so that competition will exist between the sperm of different males to fertilize a given female's eggs (Tomkins & Simmons, 2000). Secondly, hornless sneaks can outnumber horned males by as much as 80% (Hunt et al, 1999), so that horned males can have a high risk of being cuckolded.…”
Section: Introductionmentioning
confidence: 99%
“…In male dimorphic species, minor or hornless males adopt the alternative mating tactic of sneaking copulations with females that are guarded by major or horned males (17,18,20). In the species that have been studied, a male's fertilization success depends on the amount of sperm inseminated relative to other males (21,22), an assumption made in sperm competition game theory (3), and the proportion of sneak males in a population is associated with both the relative sizes of the testes, and the numbers of sperm produced (23), suggesting that sperm competition favors large testes size in these beetles. Thus, onthophagine beetles appear to have experienced a history of selection for significant investment into both horns and testes and for this reason are ideal for testing for a developmental allocation trade-off between these traits.…”
mentioning
confidence: 99%